Laparoscopic treatment of the pictures non-traumatic acute abdomen - Rodríguez, Gustavo; Tellechea, Miguel; Ant´unez, Carlos; Perdomo, Máximo; Gateño, Nisso (Cirugía del Uruguay, 2002)
Laparoscopic treatment of acute non-traumatic abdomen syndrome may be safely performed in the majority of cases. Results obtained cover the treatmen of 155 patients through videolaparoscopic approach, between February 1997 and March 2001. Twenty-two patients were excluded because the laparoscopy performed was solely for the purpose of diagnosis. Seventy-two patients were women and 61 men. Average age was 45 years old, the youngest being 7 and the oldest 86. Surgery indications were: 67 acute appendicitis; 51 acute cholecystitis; 8 diffuse peritonitis (5 due to perforated gastroduodenal ulcus, 1 of appendicular origin, another of biliary origin and still another as perforative complication of diverticular colopathy); 5 acute pancreatitis of biliary origin; 1 peridiverticular abscess and 1 biliom